Vitamin E - phosphatidylethanolamine interactions in mixed membranes with sphingomyelin: Studies by 2H NMR. (September 2020) - Cavazos, Andres T.; Kinnun, Jacob J.; Williams, Justin A.; Wassall, Stephen R.
Graphical abstract: Highlights: Vitamin E orders and destabilizes PE containing bilayer membranes. Vitamin E does not show preferential interaction with polyunsaturated PE. Negative curvature induced by vitamin E may help protect polyunsaturated PE against oxidation. Abstract: Among the structurally diverse collection of lipids that comprise the membrane lipidome, polyunsaturated phospholipids are particularly vulnerable to oxidation. The role of α-tocopherol (vitamin E) is to protect this influential class of membrane phospholipid from oxidative damage. Whether lipid-lipid interactions play a role in supporting this function is an unanswered question. Here, we compare the molecular organization of polyunsaturated 1-[ 2 H31 ]palmitoyl-2-docosahexaenoylphosphatidylethanolamine (PDPE-d31 ) and, as a control, monounsaturated 1-[ 2 H31 ]palmitoyl-2-oleoylphosphatidylethanolamine (POPE-d31 ) mixed with sphingomyelin (SM) and α-tocopherol (α-toc) (2:2:1 mol) by solid-state 2 H NMR spectroscopy. In both cases the effect of α-toc appears similar. Spectral moments reveal that the main chain melting transition of POPE-d31 and PDPE-d31 is broadened beyond detection. A spectral component attributed to the formation of inverted hexagonal HII phase in coexistence with lamellar Lα phase by POPE-d31 (20 %) and PDPE-d31 (18 %) is resolved following the addition of α-toc. Order parameters in the remaining Lα phase are increased slightly more for POPE-d31 (7%) than PDPE-d31 (4%). Preferential interaction with polyunsaturated phospholipid is not apparent in these results. The propensity for α-toc to form phase structure with negative curvature that is more tightly packed at the membrane surface, nevertheless, may restrict the contact of free radicals with lipid chains on phosphatidylethanolamine molecules that accumulate polyunsaturated fatty acids.